URGENSI LITERASI EKONOMI ISLAM PADA GENERASI MUDA MUSLIM - Susiana Manisih (Jurnal Dialog, 2015)
Islamic Economics as a system and methodology has been recognized in parallel with the other economic systems. Islamic Economics based on Islamic sharia can be put into practice in all economic sectors either financial or real sectors. The rapid development of Islamic economics in Indonesia can be seen in the number of Islamic banks which outnumbers the conventional ones. Likewise on real sector, Halal label from MUI has successfully led the lifestyle of Muslim customers to purchase only halal products. Islamic economy literacy is defined as a person’s ability to understand the Islamic economy. Thus, the person has a sensitivity and critical power that allowed them to carry out economic activities in accordance with Islamic law. In short, Islamic economy literacy is defined as the awareness of practicing the Islamic economics in accordance to Islamic law.The young generation of Muslims are expected to be the pioneers of the Islamic economics development in Indonesia. The activities of Islamic economics literacy for the younger people can be done through formal education in schools, in family, and in society. Those activities are intended to raise awareness of the Muslims youth to play a role in strengthening of the Islamic economics.